Changes in left ventricular strain parameters following pediatric heart transplantation. (25th March 2018) - Godown, Justin; Dodd, Debra A.; Stanley, Michael; Havens, Corey; Xu, Meng; Slaughter, James C.; Bearl, David W.; Soslow, Jonathan H.
Abstract: STE is increasingly utilized to assess strain in a variety of pathologies. Strain measurements have demonstrated utility following HTx and may aid in the detection of rejection and CAV. Strain parameters have not been well defined in the pediatric HTx population. This study aimed to describe strain in pediatric HTx recipients compared to controls and assess changes over time. All pediatric HTx recipients with available echocardiograms (2004‐2015) without rejection or CAV were identified. Longitudinal and circumferential strain was measured at <1 month, 1 year, 3 years, and 5 years post‐transplant and compared to controls. A total of 218 echocardiograms were analyzed in 79 HTx recipients. At <1 month post‐transplant, there was a significant decrement in longitudinal strain (GLS −14.6 vs −19.2, P < .001) with concurrent augmentation of circumferential strain (GCS −27.3 vs −24.3, P = .005). By 1 year post‐HTx, all strain parameters normalized and were not significantly different from the control population. In the absence of graft complications, strain parameters did not change up to 5 years post‐transplant. Abnormal longitudinal strain parameters are present in the early post‐HTx period with a compensatory increase in circumferential strain. These changes normalize by 1 year post‐transplant and do not change over time in the absence of graft complications.